2015
DOI: 10.1063/1.4928312
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferromagnetism in liquid-phase pulsed laser ablation synthesized nanoparticles of nonmagnetic oxides

Abstract: Intrinsic Room Temperature Ferromagnetism (RTF) has been observed in undoped/uncapped zinc oxide and titanium dioxide spherical nanoparticles (NPs) obtained by a purely green approach of liquid phase pulsed laser ablation of corresponding metal targets in pure water. Saturation magnetization values observed for zinc oxide (average size, 9 ± 1.2 nm) and titanium dioxide (average size, 4.4 ± 0.3 nm) NPs are 62.37 and 42.17 memu/g, respectively, which are several orders of magnitude larger than those of previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…LAL of elemental Ti resulted in particle oxidation and the formation of TiO and Ti 2 O 3 in addition to TiO 2 with a significantly reduced bandgap . Such LAL-synthesized defect-rich TiO x crystals show the room-temperature ferromagnetism of TiO 2 NPs . Although precise adjustment of the oxidation degree during LAL remains difficult, the oxygen affinities of many metallic materials (e.g., Cu, Zn, and Sn) provide opportunities to conveniently obtain (sub)­oxides (e.g., CuO x , , ZnO x , , and SnO x , ) by LAL of pure metal targets in oxygen-containing solutions.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…LAL of elemental Ti resulted in particle oxidation and the formation of TiO and Ti 2 O 3 in addition to TiO 2 with a significantly reduced bandgap . Such LAL-synthesized defect-rich TiO x crystals show the room-temperature ferromagnetism of TiO 2 NPs . Although precise adjustment of the oxidation degree during LAL remains difficult, the oxygen affinities of many metallic materials (e.g., Cu, Zn, and Sn) provide opportunities to conveniently obtain (sub)­oxides (e.g., CuO x , , ZnO x , , and SnO x , ) by LAL of pure metal targets in oxygen-containing solutions.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…Motaung et al 16 reported that V c O and zinc vacancies (V Zn ) are the main defects and that their relative concentration decreases with an increase in particle size, resulting in a decreased ferromagnetism (FM). Singh et al 17 observed size dependent ferromagnetism, where the degree of ferromagnetism in titanium dioxide increases with an increase in the particle size, while it is reversed for zinc oxide. They explained that the origin of ferromagnetism was a consequence of exchange interactions between localized electron spin moments originating from point defects.…”
Section: Introductionmentioning
confidence: 99%
“…Tarasenka et al investigated structural defects and magnetic properties of laser-made gadolinium silicide nanoparticles . Singh and co-workers laser-synthesized TiO 2 and ZnO nanoparticles that exhibited intrinsic room temperature ferromagnetism; they attributed the observed ferromagnetism to predominant defect centers, which were single ionized oxygen and neutral zinc vacancies in ZnO and oxygen and neutral or ionized titanium vacancies in TiO 2 . Surface chemistry and defects and concomitant photoluminescent properties of millisecond pulsed laser in liquid generated ZnO nanostructures were strongly affected by laser conditions, as reported by Kulinich et al Liu and Liang et al laser-synthesized nonstoichiometric metal oxides (TiO 2– x or SnO 2– x ) with abundant surface oxygen defects .…”
Section: Introductionmentioning
confidence: 77%